2016
DOI: 10.1007/s10021-016-9980-3
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Bromus tectorum Abundance in the Western North American Sagebrush Steppe

Abstract: Bromus tectorum can transform ecosystems causing negative impacts on the ecological and economic values of sagebrush steppe of the western USA. Although our knowledge of the drivers of the regional distribution of B. tectorum has improved, we have yet to determine the relative importance of climate and local factors causing B. tectorum abundance and impact. To address this, we sampled 555 sites distributed geographically and ecologically throughout the sagebrush steppe. We recorded the canopy cover of B. tecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 51 publications
3
41
0
Order By: Relevance
“…In many arid and semi‐arid ecosystems, precipitation is the main determinant of annual plant productivity (Holmgren et al., ). As expected, cheatgrass cover increased in wet years in our focal study area, a finding consistent with many other studies from the western US (e.g., Bradley, ; Brummer et al., ). Above‐average annual precipitation can result in exceptionally tall cheatgrass that forms dense, continuous cover in the Great Basin (Bradley & Mustard, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In many arid and semi‐arid ecosystems, precipitation is the main determinant of annual plant productivity (Holmgren et al., ). As expected, cheatgrass cover increased in wet years in our focal study area, a finding consistent with many other studies from the western US (e.g., Bradley, ; Brummer et al., ). Above‐average annual precipitation can result in exceptionally tall cheatgrass that forms dense, continuous cover in the Great Basin (Bradley & Mustard, ).…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, our seasonal temperature variables derived from monthly mean values may have been too coarse to predict biological phenomena. However, other studies also have found minimum influence of temperature on cheatgrass cover, with the exception of relatively weak effects of warmer winters and warmer summers (Bradley, ; Brummer et al., ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The interaction between B. tectorum and wildfires has been the subject of several studies in the western USA (for example, Chambers et al, 2014), but less is known about similar sites without this exotic annual grass. Since our study suggests that these ecosystems may differ from the paradigm in areas dominated by B. tectorum, other sites not dominated by B. tectorum, which include a substantial area of the western USA (Brummer et al, 2016), may warrant further study.…”
Section: Discussionmentioning
confidence: 91%
“…Alternatively, our sites have a climate that is cold and wet in the winter, and they support high cover of perennial graminoids and shrubs, which may mean fuels are not as strongly limiting for wildfires in our study region as they are in warmer and drier regions. Other studies have suggested that this combination of climate makes our study area, and many other regions of sagebrush steppe in the western USA, less suitable for one of the dominant annual invasive grasses, Bromus tectorum (Brummer et al, 2016).…”
Section: Discussionmentioning
confidence: 93%